The Jewish calendar controversy of 921/2 CE - Stern, Sacha 1962-; Rustow, Marina; Vidro, Nadia; Vollandt, Ronny 1978- (Leiden Boston Brill, 2019)
Intro -- ‎Contents -- ‎Preface -- ‎Figures, Plates and Tables -- ‎Figures -- ‎Plates -- ‎Tables -- ‎Abbreviations -- ‎Editorial Policies, Manuscripts and Sigla -- ‎Part 1. Introduction -- ‎Chapter 1. The Controversy Revisited -- ‎Chapter 2. Palestinians and Babylonians in Conflict: A Narrative -- ‎Chapter 3. Discovery and Early Scholarship -- ‎Chapter 4. Manuscripts, Texts, History: A New Approach -- ‎Chapter 5. The Jewish Calendar: The Controversy Explained -- ‎Part 2. The Book of the Calendar Controversy -- ‎Chapter 6. The Book of the Calendar Controversy: Introduction -- ‎Chapter 7. The Book of the Calendar Controversy: Critical Edition -- ‎Chapter 8. The Book of the Calendar Controversy: Diplomatic Editions -- ‎Part 3. Letters and Polemics, c. 922CE -- ‎Chapter 9. Ben Meir's First Letter -- ‎Chapter 10. Saadya's Letters -- ‎Chapter 11. Letters Miscellany -- ‎Chapter 12. Babylonian Letter 1 -- ‎Chapter 13. Babylonian Letter 2 -- ‎Chapter 14. Discourse on the Midday Limit -- ‎Chapter 15. Palestinian Polemic -- ‎Part 4. Later Sources -- ‎Chapter 16. Short References and Narratives (Sahl b. Maṣliaḥ, Hayye Gaon, Elias of Nisibis, and Various Genizah Sources) -- ‎Chapter 17. Palestinian Calendar Manuals -- ‎Conclusion -- ‎Glossary -- ‎References -- ‎Index of Sources -- ‎Manuscripts -- ‎Texts -- ‎General Index -- ‎Plates.
Description based on publisher supplied metadata and other sources
Keywords: Cultural Studies; History; tijdrekening; kalenders; jodendom